STAR TREK: TRANSHUMANISM, GENETIC MODIFICATIONS,FUNDAMENTAL RIGHTS, AND PROPORTIONALITY TEST - del Valle Quintana, Jorge Luis (2024)
Transhumanism, a movement advocating for human enhancement through emerging technologies, raises ethical and legal issues of great relevance in modern society. This approach challenges our understanding of human nature and sparks debates on fundamental rights such as equality, human dignity, and personal autonomy. In this discussion, we will examine how advancements in genetic engineering and enhancement technologies pose ethical dilemmas in addressing these fundamental rights, and how legislation and ethics must evolve to tackle these challenges.